Correlation of fundamental movement skills with health-related fitness elements in children and adolescents: A systematic review - Liu, Cong; Cao, Yuxian; Zhang, Zhijie; Gao, Rong; Qu, Guofeng (Frontiers in Public Health, 2023)
Objective: To explore the impact of fundamental movement skills on health-related fitness elements (cardiopulmonary function, muscle strength and endurance, flexibility, and body composition) in children and adolescents. Methods: Six electronic databases (Web of Science, PubMed, ProQuest, Scopus, EBSCO and CNKI) were searched, and the research literature on the correlation between children's and adolescents' fundamental movement skills performance and health-related fitness published since 2002 was collected. The guidelines of STROBE and CONSORT were used to evaluate the quality of the literature, and the sources, samples, measurement methods, main results and statistical data of the study were analyzed, summarized and discussed. Results: After applying the inclusion and exclusion criteria, 49 studies were included. Sufficient research evidence supports a significant positive correlation between fundamental movement skills and cardiopulmonary function (10, 100%) and muscle strength and endurance (12, 100%), and most studies support a significant negative correlation between fundamental movement skills and body composition (28, 65.1%) and flexibility (4, 66.7%). However, a correlation between fundamental movement skills and flexibility has not been conclusively shown. In the sub item evaluation of fundamental movement skills, object manipulation, locomotor and balance skills were all significantly and positively correlated with cardiopulmonary function and muscle strength and endurance, while locomotor skills were more closely related to body composition than object manipulation skills. Conclusion: There is a significant correlation between children's and adolescents' fundamental movement skills and health-related fitness elements.